Development of macroeconomic models based on behavioral economics: issues and further research - Talavyrya М.; Dorosh, B. (Land Management, Cadastre and Land Monitoring, 2021)
The article analyzes the formation, spread and development of behavioral economics in microeconomic research, as well as its development in macroeconomic research over the past two decades. The key shortcomings of neoclassical macroeconomic models and their critique based on existing research and practical application by central bankers are highlighted. The key stages in the formation of behavioral macroeconomics, elements of which began to appear in the works of neoclassical macroeconomists, have been identified. The main arguments in favor of replacing neoclassical macroeconomic models with new behavioral macroeconomic models are presented, as well as key issues of behavioral macroeconomics and prospects for its further adoption as a basic concept for decision-making for governments. Key studies of behavioral economists on behavioral macroeconomic models, most of which are agents-based (microfoundations-based), have been identified and systematized. Based on the results of testing various behavioral models by world-renowned scientists, as well as our analysis, it is proposed to focus further macroeconomic research on behavioral models based on the activities of agents (microfoundations). Key words: behavioral economics, behavioral macroeconomics, behavioral macromodels, agents-based models (microfoundations-based)